Running and knee osteoarthritis: a systematic review and meta-analysis - Timmins, Kate A.; Batt, Mark E.; Edwards, Kimberley L. (SAGE, 2017)
Background: Osteoarthritis (OA) is a chronic condition characterized by pain, impaired function, and reduced quality of life. A number of risk factors for knee OA have been identified, such as obesity, occupation, and injury. The association between knee OA and physical activity or particular sports such as running is less clear. Previous reviews, and the evidence that informs them, present contradictory or inconclusive findings.